Pengaruh motivasi, penilaian kinerja, kompensasi terhadap kepuasan kerja karyawan PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru - Elvi Sefriani; Nuryanti '; Taufiqurrahman ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to determine the effect of motivation, performance appraisal and compensation together on employee job satisfaction PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru. To determine the effect of motivation on employee job satisfaction PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru. To determine the effect of performance on job satisfaction PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru. To find partial compensation effect on employee job satisfaction PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru. Research method used is multiple linear regression. The population of this study were employees of PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru Riau with Capem its existing underlying numbering as many as 186 people overall. Because the population is large enough, then the selected samples by using Slovin and obtained a sample of 65 respondents by simple random sampling. The results show that of respondents with respect to motivation PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru, motivation of employees at PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru rated as good. The results for the variable motivation partially significant effect on employee job satisfaction. Respondents about performance appraisal in PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru rated as good. Performance appraisals are partially significant effect on job satisfaction. Of the total respondents about the compensation of employees at PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru considered quite good. Respondents about the job satisfaction of employees at PT. Bank Riau Kepri Cabang Pasar Pusat Pekanbaru rated as good. The results for the variable compensation partially significant effect on employee job satisfaction.Keywords: Motivation, Performance Assessment, and Compensation Against Job Satisfaction